Fast skeletal muscle troponin activator CK‐2066260 mitigates skeletal muscle weakness independently of the underlying cause. Issue 6 (21st September 2020) - Cheng, Arthur J.; Ström, Jennifer; Hwee, Darren T.; Malik, Fady I.; Westerblad, Håkan
Abstract: Background: Muscle weakness is a common symptom in numerous diseases and a regularly occurring problem associated with ageing. Prolonged low‐frequency force depression (PLFFD) is a form of exercise‐induced skeletal muscle weakness observed after exercise. Three different intramuscular mechanisms underlying PLFFD have been identified: decreased sarcoplasmic reticulum Ca 2+ release, decreased myofibrillar Ca 2+ sensitivity, and myofibrillar dysfunction. We here used these three forms of PLFFD as models to study the effectiveness of a fast skeletal muscle troponin activator, CK‐2066260, to mitigate muscle weakness. Methods: Experiments were performed on intact single muscle fibres or fibre bundles from mouse flexor digitorum brevis, which were stimulated with electrical current pulses, while force and the free cytosolic [Ca 2+ ] ([Ca 2+ ]i ) were measured. PLFFD was induced by three different stimulation protocols: (i) repeated isometric contractions at low intensity (350 ms tetani given every 5 s for 100 contractions); (ii) repeated isometric contractions at high intensity (250 ms tetani given every 0.5 s for 300 contractions); and (iii) repeated eccentric contractions (350 ms tetani with 20% length increase given every 20 s for 10 contractions). The extent and cause of PLFFD were assessed by comparing the force–[Ca 2+ ]i relationship at low (30 Hz) and high (120 Hz) stimulation frequencies before (control) and 30 min after induction of PLFFD, and after an additional 5 min of rest in the presence of CK‐2066260 (10 μM). Results: Prolonged low‐frequency force depression following low‐intensity and high‐intensity fatiguing contractions was predominantly due to decreased sarcoplasmic reticulum Ca 2+ release and decreased myofibrillar Ca 2+ sensitivity, respectively. CK‐2066260 exposure resulted in marked increases in 30 Hz force from 52 ± 16% to 151 ± 13% and from 6 ± 4% to 98 ± 40% of controls with low‐intensity and high‐intensity contractions, respectively. Following repeated eccentric contractions, PLFFD was mainly due to myofibrillar dysfunction, and it was not fully reversed by CK‐2066260 with 30 Hz force increasing from 48 ± 8% to 76 ± 6% of the control. Conclusions: The fast skeletal muscle troponin activator CK‐2066260 effectively mitigates muscle weakness, especially when it is caused by impaired activation of the myofibrillar contractile machinery due to either decreased sarcoplasmic reticulum Ca 2+ release or reduced myofibrillar Ca 2+ sensitivity.